Differences as to aspects of prenatal and childbirth between black and white/brown self-declared puerperas in maternities in a capital of northeastern Brazil (Research, Society and Development, 2023)
This study aims to characterize the sociodemographic profile of self-declared black and white/brown puerperal women treated in public maternity hospitals in the city of Teresina-PI, as well as to compare aspects regarding the care received during prenatal care and during delivery. This is a descriptive cross-sectional study, approved by the institutions involved and by the Human Research Ethics Committee of the Federal University of Piauí. The research scenarios were five public maternity hospitals in the city of Teresina-PI. The sample consisted of two groups: Group I - GI with 375 self-declared black women and Group II-GII with 375 self-declared brown/white women. The instruments used were a closed questionnaire and a Biosociodemographic questionnaire. In the statistical analysis, the IBM SPSS program (version 22) was used. The Chi-Square test, which was used in the data analysis, was applied with a 95% confidence level (α=0.05). As results found, more than half of the participants in both groups are married/stable union. The GI was the one with the highest unemployment rate and the highest percentage related to income of up to one minimum wage compared to the GII. Black puerperal women seem to have a higher unemployment rate, a lower family income, receive less information about the place of delivery and a higher frequency of vaginal deliveries when compared to brown/white women.